The involvement of utilities in the development of broadband infrastructure: A comparison of EU case studies - Paolo Gerli; Marlies Van der Wee; Sofie Verbrugge; Jason Whalley (International Telecommunications Society (ITS), 2017)
Utility providers, such as energy companies and railway operators, have been long emphasised as driving competition and facilitating investment in broadband markets. Nevertheless, their involvement and contribution to broadband development has varied significantly over time. In the late 1990s, both local and national utilities engaged in the provision of broadband networks, but only few of them managed to establish themselves as major broadband providers. More recently, new projects involving national utilities have been announced in several EU countries, opening new scenarios for utilities' contribution to Next Generation Access (NGA) development. This paper aims to explore and identify the factors affecting the entry and the success of utilities in the European broadband market. Four case studies from four EU countries (Germany, Italy, Sweden and the UK) are investigated and compared, to highlight similarities and differences under the EU regulatory framework. This qualitative analysis takes into account the interaction of market, technology and policy factors, focusing on the impact of policy and regulatory measures. As a result, this paper provides fruitful insights into the relevance and effectiveness of public interventions in broadband markets. Public support and public ownership are identified as main drivers for the involvement of utilities in EU broadband markets, with regulatory measures and economies of scope exerting a limited and decreasing influence.
Keywords: 330; Utility providers; broadband investment; broadband policy; open-access networks